Estudio y diseño del sistema de agua potable, alcantarillado sanitario y pluvial de la ciudadela Nueva Kenedy, del cantón Arenillas, provincia de El Oro. - Duta Brito, Karen Ivonne (2015)
This study is a potable water system, sewer system and Stormwater, which were developed using the specifications and standards given in consultation texts found on the Internet and books. The municipality of Arenillas has decided as one of its priorities the completion of a study of a Drinking Water System, Sanitary Sewer System and Stormwater for Citadel "New Kenedy" to meeting the requirements and needs of the entire population of the sector. Based on this work will be the designs and existing data from neighboring Citadels granted by the municipality of Arenillas. The realization of this project will be in an area of ​​9.09 ha. in which the population has health problems due to lack of essential drinking water for daily living, problems caused by the rains in the winter season causing pools of water on the access roads to the citadel; Another problem is the use of simple wells and sewage collectors. The lack of drainage causes an alteration in environmental systems and to this problem is necessary to take measures to control the disposal of wastewater, representing a reduction to the problem of this citadel and mitigate damage to amiente, thereby allowing true condition of social development. The central problem of the citadel lies in not owning a water system, sewer system and Stormwater, to increase the standard of living of the locals and based on the analysis of the basic services needed, presents then: "Study and design of Drinking Water, Sewerage and Stormwater citadel" New Kenedy "canton Arenillas, El Oro province" to solve health problems to the affected community.